PENGARUH PELATIHAN DAN PENGEMBANGAN TERHADAP PRODUKTIVITAS KERJA - Ariya Fajar Baskoro, 08.05.51.0053; Muhaimin, Muhaimin (Students Journal of Economic and Management, 2012)
Human resource management is the responsibility of every manager and among those responsibilities also include training and workforce development to improve productivity. The purpose of this study was to analyze the effect of manpower training and development on employee productivity partsproduction. Sample collection technique is simple random sampling. Is the primary data type. Methods of data collection using questionnaires. The analysis technique used is multiple regression. The results of the analysis using SPSS version 20 shows that: (1).Training has positive and significant impact on labor productivity. (2).Development does not have a positive and significant impact on labor productivity. Keywords: Training, Development, Work Produktivtas